HYPNOSIS, HYPNOTIZABILITY AND RESPONSE EXPECTANCY: A CRITICAL REVIEW - Jara Vera, Pedro; Martínez Sánchez, Francisco (Anales de Psicología / Annals of Psychology, 1999)
In this essay, a review of all the research work about the role of response expectancies as a variable underlying hypnotical behavior is made. Response expectancy is a psychological variable with far-reaching repercussions. Its understanding enriches the Social Learning Theory and, like in other contexts, plays an essential role in the field of hypnotical experience. The hypotesis of the response expectancy is developed within the socio-psychological or cognitive-behavioral perspective of hypnosis and has important implications not only for the basic research of the hypnotical phenomenon, but also for the practice of hypnotherapy and psychotherapy in general.